2019
DOI: 10.1111/1365-2664.13482
|View full text |Cite
|
Sign up to set email alerts
|

Additive and interactive effects of pollination and biological pest control on crop yield

Abstract: 1. Insect pollination and biological pest control simultaneously influence crop yield, but are often investigated individually. This can lead to under-or over-estimation of the importance of individual services when they interact to affect yield. Recent, limited evidence from field studies showed contrasting results with both additive and non-additive positive and negative effects.2. To disentangle the mechanisms underlying these responses, we conducted a greenhouse experiment and a field study. We tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The higher levels of provisioning services observed in diversified systems could largely be driven by these positive effects on regulatory ecosystem services (Dainese et al, 2019; Gagic et al, 2019; Lundin et al, 2013; Sutter & Albrecht, 2016). Garibaldi et al (2018) showed that synergistic effects (positive interactions) between yield and regulatory services generally outnumber negative ones, suggesting that positive impacts of crop diversification on regulating services such as soil quality and pest control lead to the positive impacts on provisioning services observed (Garibaldi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The higher levels of provisioning services observed in diversified systems could largely be driven by these positive effects on regulatory ecosystem services (Dainese et al, 2019; Gagic et al, 2019; Lundin et al, 2013; Sutter & Albrecht, 2016). Garibaldi et al (2018) showed that synergistic effects (positive interactions) between yield and regulatory services generally outnumber negative ones, suggesting that positive impacts of crop diversification on regulating services such as soil quality and pest control lead to the positive impacts on provisioning services observed (Garibaldi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Forest proximity has been linked to higher visitation rates by pollinators and increased soybean productivity in central Argentina (Monasterolo, Musicante, Valladares, & Salvo, 2015), and these effects could be magnified with increasing amounts of non-crop habitats (Benjamin, Reilly, & Winfree, 2014). Therefore, forest cover and proximity may enhance crop yield through a synergic interaction between richer communities of natural enemies and pollinators (Gagic, Marcora, & Howie, 2019).…”
Section: Soybean Herbivory and Yieldmentioning
confidence: 99%
“…The higher levels of provisioning services observed in diversified systems could largely be driven by these positive effects on regulatory ecosystem services 3235 . Garibaldi et al, 2018 showed that synergistic effects (positive interactions) between yield and regulatory services generally outnumber negative ones, suggesting that positive impacts of crop diversification on regulating services like soil quality and pest control lead to the positive impacts on provisioning services observed 36 .…”
Section: Resultsmentioning
confidence: 99%